1996
DOI: 10.1007/bf02251781
|View full text |Cite
|
Sign up to set email alerts
|

Personality and drug testing: An exploration of the perceived fairness of alternatives to urinalysis

Abstract: ABSTRACt. Paper-and-pencil inventories have been suggested as a less invasive alternative to urinalysis drug testing. Using 702 students in three experiments, an overt integrity test, a personality inventory, an interest inventory and a no-testing control condition were compared. Subjects reacted most positively when no testing was required. When drug testing was required, subjects were most satisfied with either overt tests or urinalysis, and least satisfied with the personality inventory. Attempts to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…As a result, these types of questions diminish the transparency and perceived fairness of biographical inventories and personality inventories. Thus, they are often considered unfair (Rosse et al, 1996b;Smither et al, 1993) despite their above average ability to effectively predict candidates' job performance (Hunter and Hunter, 1984).…”
Section: Hiring For Procedural Justicementioning
confidence: 99%
“…As a result, these types of questions diminish the transparency and perceived fairness of biographical inventories and personality inventories. Thus, they are often considered unfair (Rosse et al, 1996b;Smither et al, 1993) despite their above average ability to effectively predict candidates' job performance (Hunter and Hunter, 1984).…”
Section: Hiring For Procedural Justicementioning
confidence: 99%
“…If personality testing--both in general and with specific reference to drug/integrity testing--is useful, our results point to the need to find ways to make it more acceptable to job applicants. As Rosse et al (1996) note, factors to consider in such research include using personality inventories that are designed to enhance face validity and m~nlmlze privacy invasion; providing additional explanation of the purpose of the personality measure; and expressing concern to exRmlnees about the invasiveness of the personality measure. The current study suggests that the efficacy of these techniques may be enhanced by focusing primarily on those individuals whose concerns are based on principled dissent rather than a self-interested motive of avoiding detection.…”
Section: Discussionmentioning
confidence: 99%
“…Ai~r they read all materials and completed any paper-and-pencil "tests," subjects completed a survey which assessed their reactions to the firm and its selection procedures. A complete description of the experimental procedures can be found in Rosse, Ringer and Miller (1996).…”
Section: Methodsmentioning
confidence: 99%
“…Employee judges rated the overt PSI as higher in job-relevance, and lower in offensiveness and invasiveness than either of the personality-based inventories. Similarly, Rosse, Ringer and Miller (1996) found that college student research participants that were administered an integrity test modeled on commercially available overt tests reported significantly higher impressions of the instrument than subjects that were administered an integrity test modeled after commercially available personality-based measures. It is important to note that Rosse et al (1996) intentionally over-sampled items that were relevant to drug use in order to achieve their research objectives.…”
Section: Organizational Justice and Applicant Perceptions Of Integritmentioning
confidence: 94%
“…Similarly, Rosse, Ringer and Miller (1996) found that college student research participants that were administered an integrity test modeled on commercially available overt tests reported significantly higher impressions of the instrument than subjects that were administered an integrity test modeled after commercially available personality-based measures. It is important to note that Rosse et al (1996) intentionally over-sampled items that were relevant to drug use in order to achieve their research objectives. Even so, both Jones (1991) and Rosse et al (1996) provide preliminary evidence that test takers perceive overt integrity measures as more appropriate for personnel selection than personality-based measures.…”
Section: Organizational Justice and Applicant Perceptions Of Integritmentioning
confidence: 94%